2002
DOI: 10.1007/s00439-002-0825-0
|View full text |Cite
|
Sign up to set email alerts
|

Association found between the promoter region polymorphism in the apolipoprotein A-V gene and the serum triglyceride level in Japanese schoolchildren

Abstract: The purpose of this study was to assess the influence of single nucleotide polymorphism 3 (SNP3) of the apolipoprotein A-V ( APOA5) gene on the serum triglyceride (TG) level in Japanese schoolchildren. To determine the frequency of the genotype, we analyzed 552 schoolchildren. The frequencies of the T/T, T/C and C/C genotypes of the APOA5 gene were 225 (40.8%), 263 (47.6%) and 64 (11.6%), respectively. The serum TG level was significantly different among the genotypic groups after adjustments for age, gender a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
63
1
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 11 publications
21
63
1
2
Order By: Relevance
“…Two common haplotypes were defined: APOA5*2 based on −1131C→T and APOA5*3 based on the c56C→G polymorphism [8]. Association studies have shown a positive correlation between plasma triglycerides and the rare variant of the c56C→G, as well as the rare variant of the −1131T→C in a number of different populations, patient cohorts, and ethnic groups [7,12,13,[25][26][27][28][29][30][31][32]. In the present study, the associations between these genetic variations and plasma triglycerides did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 72%
“…Two common haplotypes were defined: APOA5*2 based on −1131C→T and APOA5*3 based on the c56C→G polymorphism [8]. Association studies have shown a positive correlation between plasma triglycerides and the rare variant of the c56C→G, as well as the rare variant of the −1131T→C in a number of different populations, patient cohorts, and ethnic groups [7,12,13,[25][26][27][28][29][30][31][32]. In the present study, the associations between these genetic variations and plasma triglycerides did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 72%
“…The four common SNPs and their association with TG have shown the same effect in Caucasian, 4,7,31 African-American, 5,7 Hispanic, 5 Japanese 31,32 and Chinese 31,32 populations.…”
Section: Snps/haplotypes and Plasma Tg Concentrationmentioning
confidence: 84%
“…Moreover, whereas genetic association studies have revealed consistent association of minor APOA5 alleles with increased plasma TG levels (2,4,5,21,22), the influence of APOA5 polymorphisms on plasma TC levels is less clear. The minor allele of the APOA5 Ϫ1131T3 C promoter variant has been associated with a modest decrease of HDL cholesterol in some but not all studies (21,22) and in one study with a more pronounced increase of VLDL-cholesterol (21). Although apoAV-induced TG reduction thus may be more relevant for human lipid metabolism compared with the TC-reducing effect, the mechanism underlying the effect on HDL is intriguing.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, plasma TC levels were reported to be unaffected by the absence (apoa5 Ϫ/Ϫ mice) or overexpression (human APOA5 transgenic mice) of apoAV (2). Moreover, whereas genetic association studies have revealed consistent association of minor APOA5 alleles with increased plasma TG levels (2,4,5,21,22), the influence of APOA5 polymorphisms on plasma TC levels is less clear. The minor allele of the APOA5 Ϫ1131T3 C promoter variant has been associated with a modest decrease of HDL cholesterol in some but not all studies (21,22) and in one study with a more pronounced increase of VLDL-cholesterol (21).…”
Section: Discussionmentioning
confidence: 99%